The full magnon spectrum of yttrium iron garnet. Issue 1 (December 2017) - Princep, Andrew; Ewings, Russell; Ward, Simon; Tóth, Sandor; Dubs, Carsten; Prabhakaran, Dharmalingam; Boothroyd, Andrew
Abstract The magnetic insulator yttrium iron garnet can be grown with exceptional quality, has a ferrimagnetic transition temperature of nearly 600 K, and is used in microwave and spintronic devices that can operate at room temperature. The most accurate prior measurements of the magnon spectrum date back nearly 40 years, but cover only 3 of the lowest energy modes out of 20 distinct magnon branches. Here we have used time-of-flight inelastic neutron scattering to measure the full magnon spectrum throughout the Brillouin zone. We find that the existing models of the excitation spectrum fail to describe the optical magnon modes. Using a very general spin Hamiltonian, we show that the magnetic interactions are both longer-ranged and more complex than was previously understood. The results provide the basis for accurate microscopic models of the finite temperature magnetic properties of yttrium iron garnet, necessary for next-generation electronic devices. Yttrium Iron Garnet: neutron scattering reveals full spin-wave spectrum Complete spin-wave dispersions have been measured on a crystal of Yttrium Iron Garnet (YIG) by inelastic neutron scattering. Andrew Princep and co-workers from Oxford University (in partnership with Innovent e.V) have grown high quality YIG crystals and measure the dispersion of magnons, which are wave-like quantized collective excitations of spins, in up to energies of 120 meV using inelastic neutron scattering. They further reproduce the entire spectrum by using linear spin–wave theory, considering various forms of the magnetic exchange interactions and pathways. The analysis confirms the important role of nearest-neighbour magnetic exchange interactions, but calls for reinterpreting the nature of longer-ranged interactions. These results offer essential information on the optical magnon modes at room temperature and are of importance for technological applications of YIG.